2021
DOI: 10.1001/jamanetworkopen.2021.20052
|View full text |Cite|
|
Sign up to set email alerts
|

Experiences of Patients After Withdrawal From Cancer Clinical Trials

Abstract: Key Points Question What are the experiences of patient-participants when they leave a cancer clinical trial? Findings In this qualitative study in which 20 patients with cancer who withdrew or were withdrawn from clinical trials were interviewed, 5 themes emerged: posttrial prognostic awareness, goals of care discussions, emotional coping, burden of adverse effects, and professional trust and support. Meaning Clinical trial exit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…A study of 20 patients who withdrew or were withdrawn from cancer clinical trials showed that, in accordance with the clinical trial protocol, 13 patients (65%) were withdrawn due to disease progression. 14 Another phase 1 cancer clinical trial reported that disease progression accounted for 57.6% of the reasons for study withdrawal. 29 Disease progression is an uncontrollable factor that results in study withdrawal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 20 patients who withdrew or were withdrawn from cancer clinical trials showed that, in accordance with the clinical trial protocol, 13 patients (65%) were withdrawn due to disease progression. 14 Another phase 1 cancer clinical trial reported that disease progression accounted for 57.6% of the reasons for study withdrawal. 29 Disease progression is an uncontrollable factor that results in study withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have assessed motivations for or barriers to clinical trial participation as well as the reasons for study withdrawal by surveying the participants or physicians. 4 , 13 , 14 , 15 , 16 However, CRCs may have different perceptions, from those of other nurses or physicians, about clinical trials. 17 , 18 Nevertheless, few studies have surveyed CRCs who coordinate cancer clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, despite this mental and physical burden, they reconsider consent in the future. This new nding corresponds to the fact that patients who are in the process of stopping ECT, still hope that there will be another treatment that will cause them to avoid palliative care [13,17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the aim of this study is to explore in which extend the self-determination theory of Ryan and Deci according to the enrolment phase corresponds to the motivations of participants during ECT participation. These outcomes may support advanced care planning during trial participation and will lead to a well-informed decision-making process after trial participation [17].…”
Section: Introductionmentioning
confidence: 88%
“…In the Original Investigation titled “Experiences of Patients After Withdrawal From Cancer Clinical Trials,” 1 published August 10, 2021, there was an error in the Funding/Support statement at the end of the article. It should have stated that grant T32NR009356 to Ms Foxwell was from the National Institutes of Health.…”
mentioning
confidence: 99%